Normative determinants of effective management of municipal resources - Sebastian Krzysztof Bentkowski (Journal of Modern Science)
Objectives The purpose of this article is to present the legal determinants of effective management of municipal resources, including legal standards regulating the principles and methods of managing municipal property and finances, the obligations of entities responsible for the proper functioning of the municipal resource management system, as well as the legal basis for monitoring and assessing the effectiveness of municipal resource management.